2009
DOI: 10.1159/000260084
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Allergy in Strawberry Greenhouse Workers

Abstract: Background: Employees in strawberry greenhouses are highly exposed to several (potential) allergenic agents. However, no occupational allergy in this branch has been described before. First, the presence of work-related allergic symptoms in strawberry workers was explored. Second, we aimed to prove the concept that an IgE-mediated allergy could be responsible for work-related symptoms. To test the possibility of an IgE response secondary to cross-reactivity to birch or grass pollen, inhibition experiments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 53 publications
1
16
0
1
Order By: Relevance
“…Many plant pollens from fruit trees are entomophilous and therefore considered of low allergenic interest, except for subjects occupationally exposed [3,4]. Cases of allergic reactions to pollen from fruit trees and ornamental plants have been reported, although mainly limited to workers directly exposed or pollen that is transported by airborne particles [5][6][7][8][9]. However, in certain regions of the world fruit tree pollens can be relevant not only in exposed individuals but also in the general population, as occurs with palm tree pollen [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Many plant pollens from fruit trees are entomophilous and therefore considered of low allergenic interest, except for subjects occupationally exposed [3,4]. Cases of allergic reactions to pollen from fruit trees and ornamental plants have been reported, although mainly limited to workers directly exposed or pollen that is transported by airborne particles [5][6][7][8][9]. However, in certain regions of the world fruit tree pollens can be relevant not only in exposed individuals but also in the general population, as occurs with palm tree pollen [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Pollens from Rosaceae family have been rarely reported as a cause of occupational allergy. There are some cases among workers of strawberry and rose crops. The presence of allergens in Rosaceae fruit tree pollen has been documented by Berrens et al .…”
Section: Discussionmentioning
confidence: 99%
“…Occupational allergy due to Rosaceae pollen is rare. It may cause sensitization in exposed individuals, and it has been described as a cause of occupational respiratory allergy in workers in strawberry crops and roses, and in workers of artificial pollination of the Japanese pear or peach tree…”
Section: Introductionmentioning
confidence: 99%
“…Inhalation of frozen raspberry powder was reported to cause occupational asthma [23]. Quite recently Patiwael et al [49] reported that strawberry greenhouse workers exhibited occupational allergy, concluding that allergic symptoms among a proportion of strawberry greenhouse employees were attributable to the workplace.…”
Section: Which Allergens Are Known In Small Fruits?mentioning
confidence: 99%